Continuous vs. intermittent meropenem infusion in critically ill patients with sepsis: a systematic review and meta-analysis of randomized controlled trials with trial sequential analysis - Wang, Youquan; Li, Yanhua; Gao, Meng; Zhang, Mingtao; Li, Yuting; Wang, Dongxia; Li, Xinyu; Zhang, Chaoyang; Fu, Yao; Li, Hongxiang; Zhang, Dong (Frontiers in Medicine, 2025)
BackgroundA recent large multicenter randomized controlled trial (RCT) found that continuous infusion (CI) of meropenem did not improve clinical outcomes in critically ill patients, contradicting previous meta-analysis results.MethodsWe conducted a search of the PubMed, EMBASE, and Cochrane databases up to March 19, 2024.ResultsOur study included a total of 1,075 critically ill patients with sepsis from five RCTs. The primary outcome indicated that CI of meropenem did not reduce all-cause mortality in patients (RR = 0.89; 95% CI, 0.75–1.04; P = 0.15; Chi2= 5.75; I2 = 30%). The secondary outcomes revealed that compared to II of meropenem, patients receiving CI had shorter ICU length of stay (MD = –2.39; 95% CI, –2.98 to –1.81; P < 0.00001; Chi2= 6.63; I2 = 40%), higher clinical cure rates (RR = 1.88; 95% CI, 1.23–2.87; P = 0.004; Chi2 = 1.87; I2 = 0%), and shorter duration of meropenem therapy (MD = –0.86; 95% CI, –1.36 to –0.36; P = 0.0008; Chi2 = 3.65; I2 = 45%).ConclusionIn critically ill patients with sepsis, CI of meropenem did not reduce mortality but was associated with shorter ICU length of stays, higher clinical cure rates, and shorter duration of meropenem therapy. Further large-scale RCTs are needed to validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024528380, identifier CRD42024528380.